The Politics of Legal Facts: The Erasure of Pushback Evidence from the European Court of Human Rights - Alpes, Maybritt Jill; Baranowska, Grażyna (Law and Social Inquiry-Journal of the American Bar Foundation, 2024)
This article analyzes how the European Court of Human Rights (ECtHR) handles evidence of pushback, where states violently force asylum seekers away from borders. An examination of how the experiences of pushback survivors get translated (or not) into judgments contributes to theoretical discussions about truth, epistemic practices, and law. The article asks why so little of what researchers, journalists, civil society actors, and international organizations have documented about European border violence is visible in the court’s judgments. Based on a mix of legal and anthropological research methods, the article traces how states and the ECtHR erase pushback evidence at borders and during litigation. Taking seriously on equal grounds the construction of facts outside and inside a court room, the article connects external perspectives on the production of evidence with an internal analysis of evidence in judgments. In doing so, the article highlights the political dimensions of seemingly merely technical and legal procedures. We argue for a clearer separation of courts’ and states’ versions of facts, contending that the presumption of the states’ good faith should no longer apply when there is evidence, including in case law, of misrecordings and false statements by respondent states.
CRIS-Team Scopus Importer:2024-10-18